Potential and place of efferent therapy in patients with myocardial infarction complicated by cardiogenic shock - M. A. Kercheva; O. O. Panteleev; V. V. Ryabov (Российский кардиологический журнал)
Myocardial infarction complicated by cardiogenic shock (MI CS) is the terminal stage of the cardiovascular disease continuum, leading to the death of every second patient in its severe course. Over the past decades, there are no improvement in inhospital mortality rates for MI CS, despite the widespread introduction of early and effective revascularization methods and intensive care techniques. Recently, more and more data have emerged on the significant contribution of the systemic inflammatory response (SIR) to the pathogenesis of acute coronary syndrome and its complications. The characteristics and impact of SIR in MI CS on its course and outcome have not been sufficiently studied. One of the strategies to influence the SIR course, along with the use of anti-inflammatory therapy, is efferent treatment. However, despite all the above-mentioned fundamental prerequisites for the use of an extracorporeal therapy in CS patients, the introduction of these techniques into clinical guidelines and practice requires exploratory and multicenter randomized studies. This review article summarizes modern ideas and characterizes the existing possibilities of using efferent therapy in MI CS.